(3-x)(4-x)-2=0

Simple and best practice solution for (3-x)(4-x)-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-x)(4-x)-2=0 equation:



(3-x)(4-x)-2=0
We add all the numbers together, and all the variables
(-1x+3)(-1x+4)-2=0
We multiply parentheses ..
(+x^2-4x-3x+12)-2=0
We get rid of parentheses
x^2-4x-3x+12-2=0
We add all the numbers together, and all the variables
x^2-7x+10=0
a = 1; b = -7; c = +10;
Δ = b2-4ac
Δ = -72-4·1·10
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{9}=3$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-3}{2*1}=\frac{4}{2} =2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+3}{2*1}=\frac{10}{2} =5 $

You can always share this solution

See similar equations:

| 1x^2-7x+2=-8 | | x4-15x2=16 | | f/4+75=158 | | 5x+13+4x+12=11x+3 | | (3x+5)/4-(2x-1)/3=2 | | 5x+13+4x+12+11x+3=180 | | 13f-72=760 | | 7f+49=434 | | 6m+21/2=33/2 | | (x+10)/2+3=2 | | x+10/2+3=2 | | 6x^2-9x-56.5=0 | | 33/2x-5-3=1/4 | | 5x+8-7x=15-17x+15x-7 | | 4(3x+4)=-4x+5 | | 6(4x-3)=9x+2 | | 5y-7+y+25=8y+20-4y | | 7c+13c=160 | | 5?(x-3)+8x=6x-5+x | | 3(1y-4)=28 | | 8.8x=44.0 | | 4x+6=-7x+1 | | 13x-9=-14 | | -7/3a=21 | | (x)+(x+1)+(x+2)=42 | | 3t2=16t-5 | | 12a^2-8a=0 | | 3a+2/5=1 | | x+15+9x-9=90 | | 130*x=128 | | 9x-24=3×36 | | 8x+x+4x+2x=208 |

Equations solver categories